Leadership Models in the Gamification Context – Case Study - Pereira, J.; Lopes da Costa, R.; Borges, J.; Miguel, I. (International Journal of Business and Systems Research, 2021)
The present paper addresses the association of leadership quality factors and gamification, and attempts to contribute for the business management area, which is typically focused in determining correlations between leadership factors framed by literature models and behaviour analysis of leaders in the different contexts. The present investigation comprehends the following objectives: analysis of leadership models and their framework in the scope of a management simulator, and the effectiveness of gamification for organisational learning. Such objectives are achieved through: correlating operational results with leadership styles for players managing a company, to understand how the management style can and will affect the game final results, and to identify prominent leadership styles during the game. The assessed sample of gamers consisted of 92 players. At the end of the game, each player answered a leadership survey to assess leadership factors. The results obtained suggest a stronger focus on a decision making scope of traits model.